Stimuli-responsive hydrogels synthesis using free radical and RAFT polymerization - Gonçalves, Miguel A.D. (2013)
Temperature and pH stimuli-responsive hydrogel particles were synthesized using inverse-suspension polymerization in batch stirred reactor. Different water soluble co-monomers were present in the initial mixture (e.g. N-isopropylacrylamide and acrylic acid) as well as crosslinkers with different functionalities. Different operating conditions such as polymerization temperature, monomers dilution, neutralization and the initial ratios of co-monomers and monomers/crosslinker were also tried. Hydrogel particles were produced considering classical free-radical polymerization (FRP) and also RAFT polymerization. Commercially available RAFT agents 4-cyano-4-phenylcarbonothioylthio-pentanoic acid (CPA), 2-(dodecylthiocarbonothioylthio)-2-methylpropionic acid (DDMAT) and cyanomethyl dodecyl trithiocarbonate (CDT) were alternatively used. Sampling at different polymerization times allowed the study of the kinetics of polymerization through the analysis by SEC of the soluble phase. A tetra-detector array with simultaneous detection of refractive index, light scattering, intrinsic viscosity and ultra-violet signals was used in these studies. Usefulness of in-line FTIR-ATR monitoring to study the building process of such networks was also assessed. The performance of hydrogel beads was studied through drug delivery tests triggered by changes in the environmental temperature and pH. This research aims to contribute for the elucidation of the connection between the synthesis conditions, molecular architecture and properties/performance of such advanced materials.